Kombinasi Metode AHP dan Metode OCRA Pada Sistem Pendukung Keputusan Pemberian Reward Pada Karyawan - Brien A F Hutagalung (BEES: Bulletin of Electrical and Electronics Engineering, 2022)
In carrying out their work, every officer or employee certainly has competence that can be relied on. Competence becomes the provision and capital for employees to work professionally. This competency must continue to be honed and improved for employees so that employees' contributions to the agency or organization in the future will be even better. Competence is the main variable that an employee must have in carrying out his work so that the competence he has can help employees carry out their work according to predetermined targets. It is stated that competence is a basic characteristic possessed by a person that directly influences performance or can predict excellent performance. It could be said that competence is what outstanding performers do more often and more. Decision Making on Giving Rewards to PT. Matahari Department store is still not good. This is because subjective elements dominate so that employees with good performance do not have the opportunity to obtain these rewards. In order to provide rewards to employees more precisely and evenly, researchers created a more systematic program design in a Visual Basic Net application system. 2010 by applying a combination of AHP and OCRA methods, where this method makes decisions based on the highest value of each alternative and the values of previously determined criteria. A decision support system is an interactive system that supports decisions in the decision-making process through alternatives obtained from the results of data processing, information and model design using a combination of AHP and Ocra methods. A trial was carried out to enter a data sample of 10 candidates for receiving the reward. With the Decision Support System, it can provide recommendations for reward recipients based on ranking, from 10 potential reward recipients based on the highest ranking, namely: Alternative 1 with a value of 0, Alternative 2 with a value of 0.0339.